2014
DOI: 10.1155/2014/285356
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus Polysaccharide Protects Astrocytes from Being Infected by HSV‐1 through TLR3/NF‐κB Signaling Pathway

Abstract: Astragalus polysaccharide (APS) is the most immunoreactive substance in Astragalus. APS can regulate the body's immunity and is widely used in many immune related diseases. However, till now, there is little information about its contribution to the protection of astrocytes infected by virus. Toll-like receptor 3 (TLR3) is a key component of the innate immune system and has the ability to detect virus infection and trigger host defence responses. This study was undertaken to elucidate the protective effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The results pretreatment with BAY 11-7082 could increase the inhibition effects of APS on PCV2 replication by suppressing NF-B signaling pathway on the other hand. From two sides what has been discussed above, our study has showed that pre-treatment with APS inhibited PCV2 replication by suppressing NF-B signaling pathway, which was consistent with its anti-viral activity and anti-inflammation activity shown by blocking NF-B pathway [40,41]. Therefore, APS inhibit PCV2 replication by inhibiting oxidative stress and suppressing the NF-B signaling pathway.…”
Section: Discussionsupporting
confidence: 84%
“…The results pretreatment with BAY 11-7082 could increase the inhibition effects of APS on PCV2 replication by suppressing NF-B signaling pathway on the other hand. From two sides what has been discussed above, our study has showed that pre-treatment with APS inhibited PCV2 replication by suppressing NF-B signaling pathway, which was consistent with its anti-viral activity and anti-inflammation activity shown by blocking NF-B pathway [40,41]. Therefore, APS inhibit PCV2 replication by inhibiting oxidative stress and suppressing the NF-B signaling pathway.…”
Section: Discussionsupporting
confidence: 84%
“…3a ). We assumed that this might be related with the non-unique activation of TLR4 molecules in the presence of APS [ 1 ]. Also, chMyD88-dependent pathway could be stimulated by all TLRs.…”
Section: Resultsmentioning
confidence: 99%
“…Astragalus polysaccharide (APS), a medicinal herb, has been used for thousands years in China. Numerous studies have demonstrated that APS has a wide range of antiviral, antioxidant, anti-inflammatory, and immunoregulatory properties in mammals [ 1 4 ]. Shao et al demonstrated for the first time that APS directly interacted with Toll-like receptor 4 (TLR4) molecule [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lately, the antiviral effect of APS was detected in astrocytes infected by HSV-1. Research uncovered that APS could not inhibit the virus directly, but instead it protected astrocytes by promoting immunological function, such as markedly increasing the expression of tumor necrosis factor-α (TNF-α), interleukin6 (IL-6), Toll-like receptor (TLR3), and nuclear factor-κB (NF-κB) provoked by HSV-1 [ 60 ].…”
Section: The Pharmacodynamic Mechanism Of Tcm Against Hsv-1mentioning
confidence: 99%
“…Dpo ( 32 ) also improves the organism’s immunity against HSV-1 in a STING-dependent manner, hence contributing to a sustained and significant increase in IRF7 (interferon regulatory factor 7) [ 59 ]. Similarly, APS ( 33 ) (astragalus polysaccharide) promots immunological function by markedly increasing the expression of TNF-α (tumor necrosis factor-α), IL-6 (interleukin-6), TLR3 (toll-like receptor 3), and NF-κB provoked by HSV-1 [ 60 ]. From another perspective, IRF3 (interferon regulatory factor 3) can also be phosphorylated, and phosphorylated IRF3 activated type I interferon expression by binding to ISRE (interferon-stimulated response element) [ 76 ].…”
Section: Figurementioning
confidence: 99%